146k views
3 votes
Solve for V

6+2(4v-5)=-2(7v-4)+7v

2 Answers

6 votes
6+2(4v-5)=-2(7v-4)+7v
6+8v-10 = -14v+8 +7v
-4+8v = -7v +8
-4+4+8v = -7v + 8 + 4
8v = -7v + 12
8v+7v =-7v+7v+12
15v =12
15v/15 = 12/15
v = 4/5

check

6+2(4(4/5)-5)=-2(7(4/5)-4)+7(4/5)
6 +2(3.2-5) = -2(5.6-4)+5.6
6+2(-1.8) = -2(1.6)+5.6
6+-3.6=-3.2+5.6
2.4=2.4
User Charles Morin
by
6.9k points
2 votes
6+2(4v-5)=-2(7v-4)+7v
6 + 8v - 10 = -14v + 8 +7v
8v - 4 = -7v + 8
15v = 12
v = 12/15
v = 4/5
User Vitaliy Ulantikov
by
5.8k points